Students' Online Class Experiences Using Google Classroom Amidst the Covid-19 Pandemic - Cristie Ann L. Jaca (Randwick International of Education and Linguistics Science Journal, 2022)
The unprecedented occurrence of the Covid-19 pandemic has challenged both teachers and students to adapt to the new mode of teaching and learning using varied online platforms. This study explored the students' online class experiences using Google classroom as the primary medium for asynchronous and synchronous online classes. The study used the mixed-method research approach that employed both the quantitative and qualitative design to examine the students' online class experience using Google classroom amidst the Covid-19 pandemic. The data were collected from the two Bachelor of Secondary Education major groups in English classes during the second semester of Academic Year 2020-2021. The results were analyzed using descriptive statistics employing frequency count and percentage. Student-respondents find the Google classroom Very Helpful and Extremely Helpful in their online classes as it is convenient and provides them the leeway to do their schoolwork on their own time and at their pacing. Learning during the Covid-19 pandemic has been very challenging as state university students, especially in third world countries like the Philippines, experience limited internet connectivity and accessibility issues in online learning.